Auguste Comte : an intellectual biography. Vol. II - Pickering, Mary. (Cambridge ; New York : Cambridge University Press, 2009)
This volume explores the life and works of Auguste Comte from 1842 to 1852, when he transformed his philosophy into a religious and political movement.
Chapter 10 The Development of the Positivist MovementConclusion; Bibliography; Index
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Comte, Auguste, -- 1798-1857.; Comte, Auguste, -- 1798-1857; Philosophers -- France -- Biography; Philosophes -- France -- Biographies; Philosophers; France; Biographies; Biographies; Biographies